Intrafractional dose variation and beam configuration in carbon ion radiotherapy for esophageal cancer. Issue 1 (December 2016) - Haefner, M.; Sterzing, F.; Krug, D.; Koerber, S.; Jaekel, O.; Debus, J.; Haertig, M.
Abstract Background In carbon ion radiotherapy (CIR) for esophageal cancer, organ and target motion is a major challenge for treatment planning due to potential range deviations. This study intends to analyze the impact of intrafractional variations on dosimetric parameters and to identify favourable settings for robust treatment plans. Methods We contoured esophageal boost volumes in different organ localizations for four patients and calculated CIR-plans with 13 different beam geometries on a free-breathing CT. Forward calculation of these plans was performed on 4D-CT datasets representing seven different phases of the breathing cycle. Plan quality was assessed for each patient and beam configuration. Results Target volume coverage was adequate for all settings in the baseline CIR-plans (V95  > 98% for two-beam geometries, > 94% for one-beam geometries), but reduced on 4D-CT plans (V95 range 50–95%). Sparing of the organs at risk (OAR) was adequate, but range deviations during the breathing cycle partly caused critical, maximum doses to spinal cord up to 3.5x higher than expected. There was at least one beam configuration for each patient with appropriate plan quality. Conclusions Despite intrafractional motion, CIR for esophageal cancer is possible with robust treatment plans when an individually optimized beam setup is selected depending on tumor size and localization.